Estimation of the absolute surface air temperature of the Earth. Issue 8 (29th April 2013) - Jones, P. D.; Harpham, C.
Abstract : [1] Average temperatures for the hemispheres and the globe are generally expressed as anomalies from a base period. Most users of these data and the underlying constituent gridded datasets do not require the values in absolute degrees, but a number of users might require this additional detail. An example group of users are climate modellers, who want to directly compare their simulations with reality in absolute units. Reanalysis datasets offer opportunities of assessing earlier absolute temperature estimates, but until recently their quality over data‐sparse regions of the world was questionable. Here, we assess the latest Reanalysis (ERA‐Interim) which is available from 1979 to the present against earlier direct estimates. Globally averaged ERA‐Interim and the earlier direct estimates of absolute surface temperatures across the world are about 0.55°C different for the 1981–2010 period, with ERA‐Interim cooler. The difference is only 0.29°C for the Northern Hemisphere, but larger at 0.81°C for the Southern Hemisphere. Spatially, the largest differences come from the Polar Regions, particularly the Antarctic. Key Points: Considers the absolute surface air temperature of the Earth Indicates good agreement of earlier work with ERA‐Interim Main differences in Polar regions, especially Antarctica